Clinical Profile and Management of Oral Cancer Patients in a Tertiary Care Hospital in Bangladesh (Update Dental College Journal, 2022)
Introduction:  Oral cavity cancer is the 11th most common cancer worldwide, and the incidence rate of lip & oral cavity cancer in Bangladesh in 2020 was 8.9%. The National Institute of Cancer Research and Hospital (NICRH) is a specialized hospital for cancer patient care where all treatment modalities are available. This study was conducted in the faciomaxillary surgical oncology department (FMSO) to see the patient profile and management of oral cancer patients at NIRCH. Materials and methods: This observational study was carried out from January 2017 to December 2020 with hitopathologically proven oral cancer patients. Data of outdoor patients were collected from the OPD and tumor board registers, and indoor patient’s data were collected from the discharge register.  Relevant variables were included in the data collection, such as epidemiological features (age, sex) and clinicopathological data (primary site of tumor, disease pattern, TNM staging, presentation status, management of patients by tumor board decision, and surgical management). Collected data were summarized and analyzed by statistical package for the social science SPSS (version 24.0) and results were presented in table, chart, and graph form.Results: A total of 6869 patients were enrolled in the study, where 55% were female and 45% were male, with a male to female ratio of 0.82:1. Buccal mucosa was the most common site (44%) followed by lower gingivo-buccal sulcus (21%). Eighty-eight percent of the total cases were squamous cell carcinoma. Early-stage lesions were only 6% whereas advanced-stage lesions were 94%.  Among preoperative patients, 1992 (29%) were operable and 4877 (71%) were inoperable. The tumor board decided nearly 50% of patients for chemo-radiation, 10% for surgery and radiotherapy each. Among the operable patients, only 244 (20%) were operated on in our department in a four-year period. Conclusion: It is evident from this study that most of the patients present in the advanced stage illustrate the necessity for the inclusion of oral health care in primary health care by the government for early detection of oral cancer in Bangladesh.Update Dent. Coll. j: 2022; 12(2): 27-31